Ketahanan Varietas Unggul Baru dan Galur Isogenik Padi terhadap Penyakit Hawar Daun Bakteri pada Kondisi Lapangan - Yuliani, Dini; Suprihanto, Suprihanto; Sudir, Sudir (Jurnal Penelitian Pertanian Tanaman Pangan, 2021)
Bacterial leaf blight (BLB) is a major disease of rice in Indonesia. Cilacap District of Central Java Province and Kuningan District of West Java Province are two endemic areas of BLB. The field trial was carried out in Cilacap and Kuningan in planting season of 2017 to evaluate resistance to BLB of 20 rice genotypes including 10 new improved varieties, 1 differential variety, 9 isogenic lines. The trial was arranged in a completed block design with three replications. Data collected were: 1) Incidences and severities of BLB; 2) Resistances of the rice genotypes to BLB; and 3) Pathotypes of Xanthomonas oryzae pv. oryzae (Xoo). The results showed the incidence of BLB disease in Cilacap of 0-100% and disease severity of 0 to 85.18%. In Kuningan, the disease incidence was 0- 100% and the disease severity from 0 to 79.26%. The varieties of Inpari-32, Java-14, and the lines of IRBB-5, IRBB-7, IRBB-21, and IRBB-57 were resistant to BLB in Cilacap and Kuningan. Those varieties/lines were expected to be used as a source of resistance to BLB in Cilacap and Kuningan. Xoo pathotype test showed that 14 Xoo isolates from Cilacap classified as pathotype VIII, while nine Xoo isolates from Kuningan were classified as Pathotype III. The planting of resistant varieties based on the existence of the dominant of Xoo pathotypes which specific in the field can reduce the incidence and the severity of BLB disease effectively and efficiently, while the assembly of BLB resistant varieties can use the resistant genes of xa5, Xa7, and Xa21 as they were still effective to control the dominant pathotypes of BLB in Indonesia.